2020
DOI: 10.1002/ijop.12707
|View full text |Cite
|
Sign up to set email alerts
|

Theory of mind and loneliness: Effects of a conversation‐based training at school

Abstract: Conversation‐based training programmes are known to be effective in enhancing theory of mind (ToM). The possible consequences of such training programmes on the understanding of other constructs have rarely been investigated. The present research aimed to evaluate the effects of two different types of conversation‐based training on ToM and loneliness. Two hundred and ten fourth and fifth graders (52% boys; Mage = 9.66 years, SD = 0.85), randomly divided into two groups (ToM and no‐ToM training condition), were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…In particular, children begin to acquire morecomplex forms of false-belief understanding (Perner & Wimmer, 1985), they become more proficient in interpreting complex social situations (Baron-Cohen, O'Riordan, Stone, Jones, & Plaisted, 1999;Bosacki & Astington, 1999;Devine & Hughes, 2013;Happé, 1994), and they improve their ability to interpret mental states and emotions from facial expressions (Baron-Cohen, Wheelwright, Hill, Raste, & Plumb, 2001). Many of these aspects of advanced ToM (AToM) are closely linked to children's social competences, including feelings of loneliness or the ability to form friendships (Bosacki, Moreira, Sitnik, Andrews, & Talwar, 2020;Caputi, Cugnata, & Brombin, 2020;Devine, White, Ensor, & Hughes, 2016;Fink, Begeer, Peterson, Slaughter, & de Rosnay, 2015;Koerber & Osterhaus, 2020;Slaughter, Imuta, Peterson, & Henry, 2015). Despite its relevance for children's everyday experiences, there is a paucity of longitudinal work that narrowly tracks the development of AToM in middle childhood across multiple time points and over extensive periods of time.…”
mentioning
confidence: 99%
“…In particular, children begin to acquire morecomplex forms of false-belief understanding (Perner & Wimmer, 1985), they become more proficient in interpreting complex social situations (Baron-Cohen, O'Riordan, Stone, Jones, & Plaisted, 1999;Bosacki & Astington, 1999;Devine & Hughes, 2013;Happé, 1994), and they improve their ability to interpret mental states and emotions from facial expressions (Baron-Cohen, Wheelwright, Hill, Raste, & Plumb, 2001). Many of these aspects of advanced ToM (AToM) are closely linked to children's social competences, including feelings of loneliness or the ability to form friendships (Bosacki, Moreira, Sitnik, Andrews, & Talwar, 2020;Caputi, Cugnata, & Brombin, 2020;Devine, White, Ensor, & Hughes, 2016;Fink, Begeer, Peterson, Slaughter, & de Rosnay, 2015;Koerber & Osterhaus, 2020;Slaughter, Imuta, Peterson, & Henry, 2015). Despite its relevance for children's everyday experiences, there is a paucity of longitudinal work that narrowly tracks the development of AToM in middle childhood across multiple time points and over extensive periods of time.…”
mentioning
confidence: 99%
“…In the lowest age bracket, thirteen studies investigated socio-cognitive training in children 27 39 . Eight studies were conducted in Europe 28 , 30 , 33 37 , 39 , two studies in The United States of America 27 , 29 , one in Canada 38 , and two studies in Asia 31 , 32 . The mean age of the investigated populations in this age range was 5.98 years (range 43–60 months).…”
Section: Resultsmentioning
confidence: 99%
“…The mean age of the investigated populations in this age range was 5.98 years (range 43–60 months). N = 10 studies reported training effects in kindergarten age (range:43–60 months); n = 3 studies included older children attending elementary school (range 7–9 years) 34 , 35 , 39 . Socio-cognitive training in both groups was labelled as either ToM-training, storytelling, or metacognitive intervention with the overall aim for children to further develop socio-cognitive skills using tasks where they had to reflect on other person’s mental states and beliefs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of recursive reasoning (i.e., second-and higher-order false belief) and other linguistic measures of AToM (such as the strange stories; Happ e, 1994) have been related to diverse cognitive and social consequences, including children's ability to form friendships (Fink, Begeer, Peterson, Slaughter, & de Rosnay, 2015), their feelings of loneliness (Caputi, Cugnata, & Brombin, 2021;Koerber & Osterhaus, 2020), and academic performance, including children's reading comprehension (Lecce, Bianco, & Hughes, 2021). Individual differences in performance on social-interpretative measures have been associated with social outcomes, as well as children's everyday social experiences and their academic functioning.…”
Section: Introductionmentioning
confidence: 99%